2008
DOI: 10.1073/pnas.0710603105
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative capture of large prey solves scaling challenge faced by spider societies

Abstract: A decrease in the surface area per unit volume is a well known constraint setting limits to the size of organisms at both the cellular and whole-organismal levels. Similar constraints may apply to social groups as they grow in size. The communal three-dimensional webs that social spiders build function ecologically as single units that intercept prey through their surface and should thus be subject to this constraint. Accordingly, we show that web prey capture area per spider, and thus number of insects captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 47 publications
8
145
2
Order By: Relevance
“…Future work should include these (e.g., web architecture, size, orientation, location/elevation above ground, and silk properties) and other spider specific traits (e.g., venom properties and metabolic rates) that could affect the degree of specialization of spider–prey interactions. Similarly, social lifestyle and the construction of communal three‐dimensional webs by social spiders influence the insects captured with both sociality and colony size playing an important role in spider–prey interactions (Yip, Powers, & Avilés, 2008). In this study, half of the sheet‐tangle spiders had a social lifestyle while the other half were solitary spiders, and this could have increased variation in the prey types captured by spiders in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should include these (e.g., web architecture, size, orientation, location/elevation above ground, and silk properties) and other spider specific traits (e.g., venom properties and metabolic rates) that could affect the degree of specialization of spider–prey interactions. Similarly, social lifestyle and the construction of communal three‐dimensional webs by social spiders influence the insects captured with both sociality and colony size playing an important role in spider–prey interactions (Yip, Powers, & Avilés, 2008). In this study, half of the sheet‐tangle spiders had a social lifestyle while the other half were solitary spiders, and this could have increased variation in the prey types captured by spiders in this group.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the two more social species, A. jabaquara and A. dubiosus, do not passively filter aerial prey, but instead exhibit increased colony member participation for particular sizes of prey, perhaps to better exploit the most appropriate resources for their colony sizes. Yip et al [7] found that growing spider colonies face a scaling predicament as the threedimensional volume of the refuge area increases more quickly than the two-dimensional surface of the prey-capture web, resulting in less capture area per individual. The spiders make up for the fewer insects caught per capita by capturing increasingly large ones as colony size increases [7].…”
Section: Discussionmentioning
confidence: 99%
“…Yip et al [7] found that growing spider colonies face a scaling predicament as the threedimensional volume of the refuge area increases more quickly than the two-dimensional surface of the prey-capture web, resulting in less capture area per individual. The spiders make up for the fewer insects caught per capita by capturing increasingly large ones as colony size increases [7]. Thus, species that form large colonies are only found in lowland tropical and subtropical areas, where there is a much greater abundance of large insects than at higher elevations or latitudes [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that sigmoid inputoutput functions are not limited to interactions between cells and molecules [e.g. : Chuang et al 2010, Cornforth et al 2012, Karey & Sirbasku 1988Jourdan et al 1995, Archetti et al 2015], but have been described for behavioural interactions in animal societies, where the benefit of social interactions in a group are often non-linear (in some cases sigmoid) functions of the number of cooperative members [Rabenold 1984, Bednarz 1988, Packer et al 1990, Stander 1991, Creel 1997, Yip et al 2008]. While our argument was essentially about enzyme kinetics, and therefore we have assume that the individual players are individual cells and the population is a population !…”
Section: Importance Of the Hill Equationmentioning
confidence: 99%